SEBUAH KARYA FILM PENDEK “KASIH SAYANG” - Dimas Noercahyo; Irvan Maulana; Arryadianta Arryadianta (Inter Community: Journal of Communication Empowerment, 2019)
The development of film in Indonesia has a long journey to eventually become like a film today that is full of effects, and very easy to find as a medium of entertainment. The film has several types such as, Documentary Films, Short Films, Long Films. Short films themselves have differences with long films in terms of duration. It is said to be a short film because it is indeed short induration are 5 minutes or only 20 minutes. Not only that, the shooting process is also short, unlike widescreen films produced by professionals (Agus Dasmono, 2008: 29). The idea of this film begins from the writer wants to tell that the love ofparents will never break until the end of life, the authors also realize that young people today are not aware that the love of parents is very great for their children. This film will be a very interesting show with the story of a anxiety childwho is trusted to take care his younger brother who is still a baby and then left by his parents, making this movie useful for the community. The process of makingshort film works goes through three stages, namely pre-production, production, and post-production with the production team carrying out their duties in accordance with the jobdesk. Pre-production is the most important process, because this process will determine how to carry out the next process and the results that will be obtained. The production process takes place after preproduction is complete, production includes the process of taking pictures, organizing, and making sets. And post-production in the form of editing, sound